A novel curcumin oil solution can better alleviate the motor activity defects and neuropathological damage of a Parkinson’s disease mouse model - Geng, Xiwen; Zhang, Hao; Hu, Minghui; Liu, Xiaoyu; Han, Min; Xie, Jinlu; Li, Zifa; Zhao, Feng; Liu, Wei; Wei, Sheng (Frontiers in Aging Neuroscience, 2022)
Curcumin has been reported to improve or prevent movement disorders in Parkinson’s disease (PD); however, its low bioavailability is the biggest obstacle to its application. To optimize the limited efficacy of curcumin and to improve its protective effects against PD, we prepared and tested a novel curcumin oil solution. In vivo imaging was used to confirm that the curcumin oil solution has higher bioavailability than curcumin alone. To test its motor effects on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced movement disorders, behavioral tests, including the open-field test, pole test, rotarod test, and automated gait analysis were used. Finally, pathological evaluation using immunohistochemistry and western blotting analysis was done. Encouragingly, the behavioral test findings exhibited a better protective effect against MPTP-induced movement disorders. In addition, it had a greater protective effect on dopaminergic neurons in the compact part of the substantia nigra along with the PD process according to pathological evaluation. This novel curcumin oil solution may provide a new choice for PD prevention as a dietary supplement or clinically assisted treatment based on its better bioavailability and efficiency.